Detecting and Preventing Cheating in Exams: Evidence from a Field Experiment - Rincke, Johannes; Glogowsky, Ulrich; Cagala, Tobias (Journal of Human Resources, 2022)
This paper examines how to detect, document, and prevent plagiarism in exams. First, to identify and quantify plagiarism, we propose methods that compare similarities in multiple-choice answers between seat neighbors and non-neighbors. Second, we document cheating in undergraduate exams. Under baseline monitoring, at least 7.7% of the row-wise neighbor pairs plagiarized. Pairs composed of academically weaker students cheated more. Third, using a field experiment, we demonstrate that close monitoring eliminated cheating. By contrast, signing an honesty declaration doubled cheating relative to the control group. Complementary experiments suggest that the declaration backfired because it weakened the social norm of academic integrity.<br
Keywords: academic cheating; close monitoring; honesty declaration; field experiment; randomization testing